Reference values of mandibular condylar growth activity: a study of SUVmax with quantitative bone SPECT/CT. Issue 2 (15th November 2021) - Lin, Zefang; Xue, Qianqian; Lin, Rong; Yao, Shaobo; Miao, Weibing
Abstract : Objective: To assess the condylar growth activity (CGA) with quantitative bone single photon emission computed tomography/computed tomography (SPECT/CT) to establish reference values of maximum standardized uptake value (SUVmax ) and cutoff values for identifying active unilateral condylar hyperplasia (UCH) in different ages. Methods: We analyzed the CGA of 58 UCH patients and that of 125 volunteers as a control group by SUVmax of quantitative bone SPECT/CT imaging. The SUVmax and the uptake difference between bilateral condyles among different age groups were analyzed. SUVmax cutoff values for detecting active condyle were calculated by receiver operating characteristic curve analysis. Results: The condylar SUVmax in 10–19, 20–29, 30–39, 40–49 and 50–59 years old groups of volunteers were 6.24 ± 1.39, 4.76 ± 0.98, 3.23 ± 0.64, 3.00 ± 0.61 and 2.90 ± 0.53, respectively. The uptake difference between bilateral condyles in the control group was 3.84% ± 1.71%. The affected condylar SUVmax was significantly higher than that of the contralateral condyle in active UCH patients (6.03 ± 2.85 vs. 3.96 ± 1.07; Z = −5.264; P  = 0.000). SUVmax of the affected condyles in active UCH patients was not statistically higher than condylar SUVmax in the corresponding age group (6.03 ± 2.85 vs. 5.50 ± 1.41; Z = −0.173; P  = 0.863). SUVmax of the unaffected condyles was significantly lower than condylar SUVmax in the corresponding age group (3.96 ± 1.07 vs. 5.50 ± 1.41; Z = −5.833; P  = 0.000). SUVmax cutoff values for identifying active condyle were 6.26 and 4.53 in patients of 13–19 and 20–29 years old, respectively. Conclusions: The condylar SUVmax varied with age. Different cutoff values of condylar SUVmax should be employed for diagnosing active UCH for patients in different ages.